Understanding stress recovery and well-being through outdoor immersion within LGBTQIA+ populations - Collins, Sara-Ashley, author; LoTemplio, Sara, advisor; Dockendorff, Kari, committee member; Walker, Sarah, committee member (Colorado State University. Libraries, 2025)
This mixed-methodology study examines whether a nature environment may be a beneficial resource for stress recovery tools and source of resilience for LGBTQIA+ individuals while also assessing LGBTQIA+ experiences in nature or outdoor settings. Using a 2×3 mixed design, this study compares psychological and physiological stress recovery between 20 minutes in equivalent nature and non-nature conditions following a stress-inducing task. Overall, participants (N= 64) in the nature condition showed greater improvements in psychological stress measures (PANAS, PSS-EMA, RSQ) compared to those in the non-nature condition, with measures of affect and relaxation also improving beyond baseline levels. However, unexpectedly, physiological stress markers (RSA, RMSSD, HR) show no significant change across time points or between conditions, demanding greater attention on the potential factors contributing to this absence of coherence. Semi-structured interviews suggest that nature experiences provide numerous benefits including identity affirmation, relaxation, and community connection, but these benefits are contingent upon contexts of safe and supportive environments. Participants described positive outcomes when nature spaces felt inclusive and heightened vigilance when safety concerns arose. Collectively, these findings suggest a potential for utilizing nature-based experiences as a resilience-building tool and protective factor for LGBTQIA+ individuals who may face threats to social safety and social determinates of health while emphasizing the importance of creating explicitly safe and inclusive outdoor spaces for this community.
Keywords: mental health; outdoor recreation; stress recovery; nature immersion; LGBTQ; social safety